Pengembangan Karir dan Iklim Organisasi terhadap Komitmen Karyawan (Studi Kasus pada Bank Daerah Syariah) - Fotuho Waruwu; Dematria Pringgabayu (Masoem University, 2020)
Human Resources (HR) is a very important part in PT Bank Daerah Syariah, so that it is expected that there is an ideal and sufficient working period to optimize employee careers and increase employee commitment to the company, considering the products produced by the company are products used to facilitate the state apparatus work system and service to the wider community.This study aims to determine the effect of variable Career Development and Organizational Climate on the commitment of Employees in PT Bank Daerah Syariah. The method used in this study is a research mix method, which is a step of research by combining two forms of approach in research that is quantitative and qualitative. The population in this study were all employees in the Bank Daerah Syariah (BDS) as many as 53 employeesThe results showed that the career development variable (X1) and also the Organizational Climate (X2) had a positive and significant effect on the variable Employee Commitment (Y). The conclusion of the research shows that to increase the commitment of employees in PT Bank Daerah Syariah, the company needs to improve the existing career development system and maintain the organizational climate so that it remains conducive for all employees.